Plan de Negocios BON APPETIT (2024)
Bon Appetit is a dessert venture that aims to provide delicious and high-quality desserts to the city of Santa Marta, Colombia. The company was founded with the vision of creating a brand that represents the best of Colombian desserts, while incorporating international flavors and trends. This paper will explore the concept and vision behind Bon Appetit, the market analysis and target audience, and the execution of the business plan. The inspiration to start Bon Appetit came from the love of desserts and the desire to create a unique brand that represents the best of Colombian desserts. The founders of Bon Appetit noticed a void in the market for high quality artisanal desserts and decided to fill that void with their own products. Bon Appetit's mission statement is to provide customers with the highest quality desserts, using locally sourced ingredients and traditional techniques, while incorporating international flavors and trends. The company's core values include a commitment to quality, sustainability, and customer satisfaction. Bon Appetit's unique selling proposition is the combination of traditional Colombian flavors with international influences, resulting in a truly unique and delicious product.